Health committees in South Africa: the Influence of power on invited participation in policy and practice - Haricharan, Hanne Jensen (Department of Public Health and Family Medicine, 2019)
This study explores how the presence of multiple forms of power impact health committee participation in South Africa’s Western Cape Province in policy and practice. A qualitative case study with a rural and an urban committee is used to explore the research question. The study’s conceptual framework views health committees as invited spaces where citizens are invited to participate, in contrast to closed spaces without citizen involvement and claimed spaces where citizens claim participation. The study considers the impact of three different forms of power, namely: a) countervailing power, an external form of power, which neutralises power differentials between officials and community members; b) constraining power, which limits influence; and c) enabling power, which promotes agency. Three models for invited participation are identified: 1) Appointed participation, envisioned in the Western Cape Health Facility Boards and Committees Act (2016); 2) An organisational model, preferred by the health committees; and 3) An election model, considered in policy documents. The study found that the health committee Act provides health committees with countervailing power in the form of a mandate. However, the content of the Act ensures that the Health Department controls who participates through ministerial appointments and limits health committees’ influence through stipulating narrow roles. The practiced organisational model generates countervailing power through a claim to represent communities, but this claim is challenged by weak community links and accountability mechanisms and the fact that only organised sections are represented. Furthermore, the study demonstrates that absence of countervailing power and presence of constraining forms of power limit health committees’ influence, though they also draw on enabling forms of power. In addition, the study demonstrates that when citizens have limited influence in invited spaces, they consider creating claimed spaces. Finally, the study argues that a model with elected community representatives may provide stronger countervailing power as elections may enable health committee representatives to claim to represent the entire community. The thesis concludes that invited participation may generate sufficient countervailing power when it is legislated and based on a human rights approach, which positions committees as claim-makers and the state as duty-bearer. Furthermore, it concludes that both countervailing power and enabling power is necessary for effective substantive participation.